2004
DOI: 10.1029/2004ja010504
|View full text |Cite
|
Sign up to set email alerts
|

Plasma patch structuring by the nonlinear evolution of the gradient drift instability in the high‐latitude ionosphere

Abstract: [1] Results from the three-dimensional nonlinear simulations of the gradient drift instability to study structuring in high-latitude plasma patches are presented. Simulations demonstrate that the existence of the mesoscale structures (10 km to 100 m) on both leading and trailing edges and inside a patch is due to (1) the nonlinear development of the gradient drift instability (GDI) or due to (2) occasional reversal of the direction of convection. The high-resolution simulation data have a dynamic range that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 30 publications
(85 reference statements)
4
66
2
Order By: Relevance
“…A polar cap patch typically has a density that is 2-20 times larger than the surrounding background electron density and its horizontal size ranges from 100 to 1000 km (e.g., Tsunoda 1988, Crowley et al 2000. The convecting patches develop intermediate-scale irregularities by action of the gradient-drift instability mechanism (Kersley et al 1995), that is also confirmed by numerical simulation (Gondarenko and Guzdar 2004). Because of the steep plasma density gradients and irregularities at their edges (Weber et al 1986), the TOI structure and polar cap patches can be detected with GPS measurements (e.g., Aarons 1997;Noja et al 2013;van der Meeren et al 2014).…”
Section: Resultsmentioning
confidence: 67%
“…A polar cap patch typically has a density that is 2-20 times larger than the surrounding background electron density and its horizontal size ranges from 100 to 1000 km (e.g., Tsunoda 1988, Crowley et al 2000. The convecting patches develop intermediate-scale irregularities by action of the gradient-drift instability mechanism (Kersley et al 1995), that is also confirmed by numerical simulation (Gondarenko and Guzdar 2004). Because of the steep plasma density gradients and irregularities at their edges (Weber et al 1986), the TOI structure and polar cap patches can be detected with GPS measurements (e.g., Aarons 1997;Noja et al 2013;van der Meeren et al 2014).…”
Section: Resultsmentioning
confidence: 67%
“…The most often referenced explanation is the effect of neutral winds, which may be very important at high latitudes, especially during substorm activity and in the regions where the convective plasma flow is not uniform, e.g., close to the boundaries of auroral oval (Tsunoda, 1988). Recently, Gondarenko and Guzdar (2004) performed the threedimensional simulations of the gradient drift instability to study structuring of patches. They have shown that instability originating at the trailing edge of patches in the later phase of the nonlinear evolution spreads over the whole patch.…”
Section: Resultsmentioning
confidence: 98%
“…Solving the full electron momentum equation in fully numerical modeling efforts is computationally intensive, and this is one reason why the electron continuity equation and the vorticity equation are often used in modeling of plasma structuring processes [Gondarenko and Guzdar, 2004]. In the above analysis, both were included or excluded.…”
Section: General Case: Importance Of Inertial Effectsmentioning
confidence: 99%